B, N-doped ultrathin carbon nanosheet superstructure for high-performance oxygen reduction reaction in rechargeable zinc-air battery - Zhao, Ruopeng (2021)
Rational structure design, composition control and heteroatom doping are efficient strategies to achieve excellent electrocatalysts for the oxygen reduction reaction (ORR) in fuel cells or metal-air batteries. Herein, a facile and efficient approach to prepare ultrathin carbon nanosheet superstructure (BN/C) with high B, N-doping level by using sodium chloride (NaCl)-assisted pyrolysis method is proposed. The developed BN/C catalyst exhibits good catalytic activity for ORR in alkaline medium with a half-wave potential (E½) of 0.8 V, which is comparable to that of commercial Pt/C. The BN/C catalyst also shows much better long-term stability and satisfactory tolerance for the methanol crossover effect. This excellent performance is attributed to the structure and composition characteristics of BN/C, including the large surface area (1085 m² g⁻¹), hierarchically porous structure, the synergistic effect of the B, N co-doping and high content of ORR active species. Significantly, the B element with electron-deficient property in BN/C can create more charged sites favorite for O₂ adsorption and thus accelerate reaction kinetics in ORR. Furthermore, a rechargeable Zn-air battery device comprising BN/C catalyst and RuO₂ with a liquid electrolyte shows superior performance with an open-circuit potential of ∼1.36 V, a peak power density of ∼115 mW cm⁻², as well as excellent durability (1000 cycles for 14 days of operation). Moreover, a flexible solid-state Zn-air battery containing BN/C catalyst and RuO₂ shows good cycling durability under different bending states, indicating the excellent practicability in wearable devices.